Parallel and series multi-bed pressure swing adsorption processes for H-2 recovery from a lean hydrogen mixture - Park, Yongha; Kang, Jun-Ho; Moon, Dong-Kyu; Jo, Young Suk; Lee, Chang-Ha (ELSEVIER SCIENCE SA, 2021)
The demand for clean energy sources has made H-2 recovery from various lean hydrogen mixtures increasingly attractive. In this study, parallel and series pressure swing adsorption (PSA) processes were investigated experimentally and theoretically, and > 99% pure H-2 was produced from a lean hydrogen mixture (H-2:CO:N-2: CO2 = 19.9:0.1:44.6:35.4 mol%) at 10 bar. A mathematical model for a PSA process using activated carbon and zeolite 13X was simultaneously validated with results from breakthrough experiments and a parallel two-bed PSA process. The parallel two-bed PSA process using a layered bed (lower bed: activated carbon, upper bed: zeolite 13X) experimentally produced H-2 with a purity of 94.6-98.3% and a recovery of 33.5-63.2%; CO was not detected in the H-2 product. In the parallel four-bed PSA process, the H-2 recovery was drastically increased to 77.3% due to an additional pressure equalization step, but the increase in H-2 purity was minute. The series PSA process, which was divided into the bulk separator and the purifier, was theoretically studied under various operating conditions. The series threeand four-bed PSA processes could produce H-2 with over > 99% purity and a recovery of 62.478% and 82.643%, respectively, due to the additional pressure equalization step and the utilization of blowdown gas. The parallel four-bed PSA process showed the highest H-2 productivity (33.58 mol(H2) (-1)(kgads) day(-1)), while the series four-bed PSA process achieved an H-2 productivity of 23.96 mol(H2) (-1)(kgads) day(-1) with > 99% H-2 purity.
Keywords: GASIFICATION COMBINED-CYCLE; COKE-OVEN GAS; PERFORMANCE ANALYSIS; ACTIVATED CARBON; ZEOLITE 13X; PURIFICATION PROCESS; PSA; CO2; SEPARATION; KINETICS